Cryopreservation of Reproductive Cells and Embryos of Laboratory, Agricultural and Wild Animals - Kopeika, Eugeniy F.; Petrushko, Maryna P.; Piniaiev, Volodymyr I.; Yurchuk, Taisiia O.; Pavlovich, Olena V.; Mikson, Konstantin B.; Butskyi, Kyrylo I.; Hapon, Hanna O.; Puhovkin, Anton Yu. (Problems of Cryobiology and Cryomedicine, 2019)
This review describes the state of the art in cryopreservation of spermatozoa, oocytes and animal embryos. We have analyzed methodical approaches for the eï¬€ective low-temperature preservation of the genetic resources of animal world and speciï¬ed the procedures of cryopreservation of animal gametes and embryos. The history of eï¬ƒcient cryopreservation for animal reproductive cells and embryos was described. To date the germ cells and embryos of many laboratory, agricultural and wild animals have been successfully cryopreserved, nevertheless there is still pending the issue with the oocytes and embryos of some species of birds, ï¬ shes and mammals. The paper discusses the ways for developing the methods to preserve the genetic material of those species that have not been successfully cryopreserved yet. Â Probl Cryobiol Cryomed 2019; 29(1): 003â€“018